Sample sizes based on three popular indices of risks. Issue 3 (5th December 2018) - Wang, Hongyue; Wang, Bokai; Tu, Xin M; Liu, Jinyuan; Feng, Changyong
Abstract : Sample size justification is a very crucial part in the design of clinical trials. In this paper, the authors derive a new formula to calculate the sample size for a binary outcome given one of the three popular indices of risk difference. The sample size based on the absolute difference is the fundamental one, which can be easily used to derive sample size given the risk ratio or OR.